Columbo caution : murder can be hazardous to your health. ([United States s.n., 1991)
A popular TV host is in danger of losing his job if his producers discovered that he made a pornographic film when he was younger, so he murders the person trying to blackmail him through an ingenious method.
VHS.
Peter Falk, George Hamilton.
Keywords: Columbo, Lieutenant (Fictitious character).; Detective and mystery films; Feature films -- United States